Oseltamivir-resistant pandemic (H1N1)2009 in Yemen - case report - Thabet, Ahmed AK (BioMed Central, 2010)
BACKGROUND: During the influenza season of 2007-08, oseltamivir-resistant influenza A (H1N1) viruses emerged in several countries in Europe, North America, and Asia. Despite substantial prevalence of oseltamivir-resistant viruses, few data are available on the clinical profile of subjects infected with these viruses. Objectives: to describe the first oseltamivir-resistant (H1N1) influenza virus pandemic 2009 from the Eastern Mediterranean Region including Yemen and to determine the evidence by clinical presentation of children infected with these oseltamivir - resistant viruses. METHODOLOGY: History, physical examination and laboratory investigations including Complete Blood Count, chest x-ray, blood cultures, CSF examination, LFTs, RFTs, blood for sugar, H1N1 test and oseltamivir resistance test. RESULTS: Nasal swabs indicated positivity on both H1N1 test and the RNP gene (Human R Nase P gene that serves as internal positive control for Human RNA. Both clinical specimens presented the mutation S31N in the M2 gene associated with resistance to adamantanes and H274Y in NA gene associated with resistance to oseltamivir. This was the first diagnosed case of resistance to oseltamivir in Yemen and also it is the first reported case of oseltamivir resistance virus in the Eastern Mediterranean Region. CONCLUSION: The pattern of resistance found in the oseltamivir resistant isolate collected from Yemen is the same as has been reported elsewhere in other WHO regions. Clinical description and outcomes are not different from what is described elsewhere.